The Effect Of Financial Attitude On Personal Financial Management: Financial Literacy As A Mediating Variable: (Study on Parking Attendant, Malioboro Area, Yogyakarta City) - Bangun Putra Prasetya; Ainun Hertikasari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Yogyakarta City is a City of Culture and Tourism City in Indonesia. The purpose of optimizing the tourism sector is to improve community welfare by utilizing facilities and infrastructure, one of which is a parking lot. The revitalization of parking locations indicates a decrease in the income level of parking attendants around Malioboro. Therefore, efforts are needed to achieve personal financial management based on Financial Attitude and Financial Literacy. This research method uses quantative with parking attendant respondents around the Malioboro area. Data analysis using SEM. The results show that financial attitude affects personal financial management, financial attitude affects financial literacy and financial literacy affects personal financial management. But financial literacy cannot mediate between financial attitudes towards Personal Financial Management.